Does product familiarity matter for participation? - Nicola Fuchs-Schündeln; Michael Haliassos (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
Household access to financial products is often conditioned on previous use. However, banning access when learning is possible may be discriminatory or counterproductive. The 'experiment' of German reunification (exogenously) offered to East Germans unconditional access to (exogenously) unfamiliar capitalist products. Controlling for characteristics, East Germans participated immediately, were as likely to use unfamiliar risky securities as West Germans, and more likely to use consumer debt, without signs of regret. Our results suggest that mistakes of unfamiliar households can be prevented by a knowledgeable and well-incentivized financial sector and by interaction with familiar peers. This implies that regulation should refocus on the financial sector rather than on prohibiting individuals to gain familiarity with financial products.
Keywords: G11; E21; 330; Household finance; familiarity; regulation; investor protection; financialliteracy; stockholding; household debt; consumer credit; social interactions; counterfactual analysis; German reunification